FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KEUANGAN MAHASISWA - Ramadhan, ZUlfikar; Prakoso, Fajar Adi; Taufan, Januar; Fairuz, Najla; Wahidah, Nur Rachmah (Taksasila Edukasi Insani, 2025)
This study aims to determine differences in student financial behavior in terms of gender, age, and parental income. The research sample was students who live in Tangerang Sealtan and were taken randomly. Data were processed using two-way ANOVA (Analysis of variances). The results of the analysis and discussion concluded that gender has a significant difference in the financial behavior of students, male students are better at managing finances compared to women. Then age has a significant difference in student financial behavior, students aged 21-22 years tend to have better financial skills compared to younger age groups, which reflects an increase in financial capability with age. While parental income does not have a significant difference in student financial behavior between parental income below Rp 5,000,000, parental income between Rp 5,000,000 to Rp 10,000,000, and parental income above Rp 10,000,000 in terms of financial behavior. Keywords : gender, age, parental income, financial behavior